The The Government Language Style Variation on Covid-19 Post in Instagram - Farida Romaito Pohan; Septiani Pohan (ITScience (Information Technology and Science), 2021)
This research aim's to investigate language style variation used by the government on a covid-19 post on Instagram. This research is applied the descriptive qualitative method that focused on two objectives of the study. Firstly, to investigate situations types of language style variation were found in social media and secondly, to investigate realized of language style variation in social media in posting Coronavirus disease (covid-19). The data were collected through caption by the government that related to covid-19 found in Instagram. The data were collected through identified language style, do note-taking, and collecting references related to data. The researcher used Martin Joss's theory (1976: 153-155) to analyze the type of language styles such as are formal style, consultative style, and casual style. The research finding showed that 8 data were used by the government in a formal style, 7 data were used by the government in a consultative style, and 5 data were used by the government in a casual style.